Circulating Tumour Cell Release after Cement Augmentation of Vertebral Metastases - Malte Mohme (Nature Portfolio, 2017)
Abstract Cement augmentation via percutaneous vertebroplasty or kyphoplasty for treatment of spinal metastasis is a well-established treatment option. We assessed whether elevated intrametastatic pressure during cement augmentation results in an increased dissemination of tumour cells into the vascular circulation. We prospectively collected blood from patients with osteolytic spinal column metastases and analysed the prevalence of circulating tumour cells (CTCs) at three time-points: preoperatively, 20 minutes after cement augmentation, and 3–5 days postoperatively. Enrolling 21 patients, including 13 breast- (61.9%), 5 lung- (23.8%), and one (4.8%) colorectal-, renal-, and prostate-carcinoma patient each, we demonstrate a significant 1.8-fold increase of EpCAM+/K+ CTCs in samples taken 20 minutes post-cement augmentation (P < 0.0001). Despite increased mechanical CTC dissemination due to cement augmentation, follow-up blood draws demonstrated that no long-term increase of CTCs was present. Array-CGH analysis revealed a specific profile of the CTC collected 20 minutes after cement augmentation. This is the first study to report that peripheral CTCs are temporarily increased due to vertebral cement augmentation procedures. Our findings provide a rationale for the development of new prophylactic strategies to reduce the increased release of CTC after cement augmentation of osteolytic spinal metastases.